Anharmonic effective potential and XAFS cumulants for hcp crystals containing dopant atom - Hung, Nguyen Van; Hau, Le Thi Thuy; Tien, Tong Sy (VNU Journal of Science: Mathematics - Physics, 2007)
A nevv procedure for calculation and analysis of XAFS (X-ray Absorption Fine Structure) cumulants of hcp crystals containing dopant atom has been derived based on quantum statistical theory with generalized anharmonic corTelated Einstein model. Analytical expressions for eíĩective local force constants, correlated Einstein frequency and temperature, first cumulant or net thermal expansion, second cumulant or Debye Waller factor and third cumulant of hcp crystals containing dopant atom have been derived. Morse potential parameters of pure crystals and those with dopant included in the derived expressions have been calculated. Numerical results for Zn doped by Cd are found to be in good agreement with experiment.